Mechanism of surfactant effect on bacterial adsorption during bioleaching of lepidolite - Xu, Chao; Zhao, Xingqing; Duan, Huaiyu; Gu, Wei; Zhang, Du; Wang, Rucheng; Lu, Xiancai (Applied clay science, 2025)
Direct contact of bacteria with minerals can provide better leaching effect than indirect contact in the process of bioleaching. As a leaching assistant, surfactant can change the surface tension of ore leaching solution, improve the bacterial adsorption capacity and enhance the biological leaching effect. Thus, this study investigated the mechanisms by which chemical and biological surfactants influence bacterial metabolism, bacterial adsorption, and leaching in the bioleaching process of lepidolite. With the addition of the biosurfactant rhamnolipid and chemical surfactants sodium dodecyl sulfate and Tween-20, FTIR of leaching residues indicated that non-polar functional groups appeared, and the contact angles decreased from 75.22° to 10.64°, 6.8°, 43.18°. Surfactants reduced the surface tension at the solid-liquid interface through the combined action of their hydrophilic head groups and hydrophobic tail groups, thereby increasing the contact area and adsorption efficiency between bacteria and minerals. Additionally, surfactants weaken the chemical bonds of mineral metals and promote the complexation of -COOH and -OH groups in organic acids with minerals. Surfactants-assisted bacterial attachment altered mineral lattice structure via microenvironment creation and bacterial metabolized organic acids. [Display omitted] •Bacterial effective adsorption resulted in the efficient lithium extraction.•Hydrophilic and hydrophobic groups of surfactants mediated bacterial adsorption.•Surfactants weaken chemical bonds of mineral metals.•Biosurfactants showed the advantages of high efficiency and environment friendly.